State Policy and Local Resistance: The History of Marijuana Prohibition in Lamteuba, Aceh (1976-2020) - Levina, Melvin; Midawati, Midawati (Laboratorium Sejarah, Departement Ilmu Sejarah, Fakultas Ilmu Budaya, Universitas Andalas, 2025)
This study analyzes the impact of the prohibition of marijuana cultivation after the implementation of the top-down policy on the local community in Lamteuba. This research applies the four stages of historical methods. The first method, heuristics, involves collecting written sources and oral sources. The second stage is source criticism. A thorough verification and evaluation were done on the collected data, followed by interpretation of the verified sources. The final stage is historiography. The study discovers that the locals of Lamteuba traditionally used marijuana for local needs. However, these practices conflicted with the law established by the central government starting in 1976, which prohibits the use of marijuana. The policy is contrary to local customs. This research is expected to contribute to research in the fields of political history and cultural history, particularly in understanding the cultural impacts of legal prohibitions imposed by authorities.